Artificial Intelligence in Islamic Education to Develop Students' Critical Thinking: Kecerdasan Buatan dalam Pendidikan Agama Islam untuk Mengembangkan Pemikiran Kritis Siswa - Hanifaa, Ummi; As’ad, As’ad (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The integration of digital technology in education continues to transform instructional methods and learning outcomes. Specific Background: In the context of Islamic Religious Education (PAI), the adoption of Artificial Intelligence (AI) remains underexplored despite its potential to enhance pedagogical effectiveness. Knowledge Gap: Limited empirical studies have addressed how AI tools impact students' cognitive engagement, particularly in fostering critical thinking within religious education settings. Aims: This study aims to analyze the use of AI in PAI learning and evaluate its contribution to the development of students’ critical thinking skills. Results: Conducted as a qualitative case study at SMPS Nurhasanah Medan, the research revealed that teachers are beginning to integrate AI tools—such as ChatGPT and digital Qur’an applications—into their teaching. Students reported increased understanding, motivation, and critical engagement. Novelty: The study highlights AI as a catalyst for higher-order thinking in religious instruction, an area seldom examined in prior literature. Implications: These findings underscore the need for strategic support, including infrastructure development, teacher training, and policy alignment, to fully harness AI’s educational benefits in PAI. Highlights: Enhances critical thinking in PAI learning. Positive student response to AI integration. Requires infrastructure and teacher training. Keywords: Artificial Intelligence, Islamic Education, Critical Thinking, ChatGPT, Educational Technology